2001
DOI: 10.1002/ajmg.1178
|View full text |Cite
|
Sign up to set email alerts
|

Misclassification risk of patients with bilateral cleft lip and palate and manifestations of median facial dysplasia: A new variant of del(22q11.2) syndrome?

Abstract: The generic term median facial dysplasia (MFD) describes a subgroup of patients with cleft lip and palate exhibiting characteristic craniofacial defects: (1) short prolabium, (2) absence of frenulum labii, (3) hypoplasia of premaxilla, (4) absent upper central and lateral incisors of the cleft side, and (5) deficient septal cartilage and nasal spine. Gross brain malformations are usually absent in MFD. The same craniofacial malformations are also described in patients with holoprosencephaly sequence (HPE-S). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…There may be a cryptic subcentromeric deletion in 22q due to an unbalanced translocation. Interestingly, 22q11.2 microdeletion has previously been reported in HPE probands (Schulze et al, 2001). However, in our case, we found no microdeletion in the 22q11.2 region with the used probe.…”
Section: Discussioncontrasting
confidence: 48%
“…There may be a cryptic subcentromeric deletion in 22q due to an unbalanced translocation. Interestingly, 22q11.2 microdeletion has previously been reported in HPE probands (Schulze et al, 2001). However, in our case, we found no microdeletion in the 22q11.2 region with the used probe.…”
Section: Discussioncontrasting
confidence: 48%
“…Genetic aspects of frontonasal dysplasia are not well-defined. Although frontonasal dysplasia occurs sporadically in most of the cases, autosomal dominant and X-linked patterns, as well as 22q11 microdeletion have been reported in the literature (1,10,11). In general, the possibility of this syndrome occurring in the next sibling is suggested to be 25% (12).…”
Section: Discussionmentioning
confidence: 99%
“…FND occurs sporadically (DeMeyer, 1967;Sedano et al, 1970;Guinon-Almeida et al, 1996), but some familial cases have been reported. Recently, autosomal dominant (Fryburg et al, 1993;Qureshi and Naeem-uz-Zfar, 1996;Nevin et al, 1999) and X-linked dominant inheritance (Fryburg et al, 1993;Nevin et al, 1999) have been suggested in some families, while 22q11 microdeletions have been detected in a few patients (Schultze et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A normal male karyotype was found at amniocentesis. FISH analysis for the detection of 22q11 microdeletion was not performed (Schultze et al, 2001). After prenatal counseling, the couple opted for termination of pregnancy and a pathological examination was performed.…”
Section: Case Reportmentioning
confidence: 99%